Education for International Understanding and Design Literacy - Li, Xiaoyu (Formakademisk, 2024)
In this paper the integration of international understanding into design education will be discussed. Through an exposition of UNESCO's concept of Education for international understanding. I will discuss the fundamental goal of promoting world peace and the artistic vision of “understanding”. It will discuss what positive educational explorations and practices design education can undertake to expand the humanistic connotations of international understanding, promote intercultural understanding, and peaceful and friendly development, and what basic qualities it should cultivate.